Factors that Influence the Decision in Using Social-Media as a Media for Buying and Selling Transaction - Rinabi Tanamal (Teknik Informatika Universitas Pamulang, 2021)
There are many uses of technology and the use of technology used in everyday life. One of the uses of technology is social media, ranging from facebook, Twitter, Instagram and many more. Increased use of social media can change everyone's lifestyle. Facebook is one of the social media that has its own benefits and functions. In this study, examined the part of Facebook where the use of facebook as a buying and selling transaction. The use of facebook as a medium of buying and selling transactions has become commonplace for the people of Indonesia, judging by the data in 2019 facebook users reached 120 million users. The purpose of this research is to find out the influence of variable trust, transaction quality and satisfaction on intention to use. With this, researchers used Structural Equation Modeling-Partial Least Square (SEM-PLS) method as an analysis technique for relation patterns between variables in the study. The results showed that trust has the highest value of relationships or relationships of 0.710 compared to transaction quality and satisfaction. This indicates that the level of trust is very influential on the intention of use and this is usually one of the benchmarks in conducting buying and selling transactions.